2013
DOI: 10.1088/0004-637x/773/2/112
|View full text |Cite
|
Sign up to set email alerts
|

Newly Quenched Galaxies as the Cause for the Apparent Evolution in Average Size of the Population

Abstract: We use the large COSMOS sample of galaxies to study in an internally self-consistent way the change in the number densities of quenched early-type galaxies (Q-ETGs) of a given size over the redshift interval 0.2 < z < 1 in order to study the claimed size evolution of these galaxies. In a stellar mass bin at 10 10.5 < M galaxy < 10 11 M , we see no change in the number density of compact Q-ETGs over this redshift range, while in a higher mass bin at >10 11 M , where we would expect merging to be more significan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
397
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(431 citation statements)
references
References 88 publications
28
397
2
1
Order By: Relevance
“…This results in galaxies which are quenched earlier in the history of the Universe having smaller sizes for their masses, and hence higher central mass concentrations and presumably central velocity dispersions. Therefore, it is possible that the observed strong correlation between quenched fraction and central velocity dispersion is in some sense tautologous, when the size evolution is taken into account (as first argued for in Carollo et al 2013;Lilly & Carollo 2016). It remains to be seen in detail if size evolution alone can lead to the observed trends witnessed in this work.…”
Section: Alternative Explanations To Agn Feedback and Green Valley Fracmentioning
confidence: 74%
“…This results in galaxies which are quenched earlier in the history of the Universe having smaller sizes for their masses, and hence higher central mass concentrations and presumably central velocity dispersions. Therefore, it is possible that the observed strong correlation between quenched fraction and central velocity dispersion is in some sense tautologous, when the size evolution is taken into account (as first argued for in Carollo et al 2013;Lilly & Carollo 2016). It remains to be seen in detail if size evolution alone can lead to the observed trends witnessed in this work.…”
Section: Alternative Explanations To Agn Feedback and Green Valley Fracmentioning
confidence: 74%
“…Instead, given that quenched galaxies at a given mass are observed to be smaller than star-forming ones, the quenched population size growth can be achieved merely by the continuous addition of larger star-forming galaxies as more and more of them quench over time (van Dokkum & Franx 2001;Carollo et al 2013). The picture that emerges from the study presented here is that individual quenched galaxies do indeed grow in size over cosmic time, but as a population they do so at a rate that does not differ very substantially from individual main-sequence galaxies for most of cosmic time.…”
Section: Discussionmentioning
confidence: 99%
“…The typical size of galaxies with any given selection criteria (and in particular, quenched galaxies in a given mass bin) will evolve with time due to two factors: i) the size evolution of individual galaxies that correspond to the selection, and ii) the transition of galaxies into and outside of the selection. A particular scenario within this context that is extensively debated in the literature is 'progenitor bias', according to which the time evolution of the typical size of quenched galaxies is driven by the appearance of new, large quenched galaxies as a result of the ongoing quenching of (large) star-forming galaxies (Carollo et al 2013;Cassata et al 2013;Krogager et al 2014;Bruce et al 2014). Other studies concluded however that 'progenitor bias' is sub-dominant compared to the size growth of individual galaxies (Hopkins et al 2010;Bernardi et al 2011;Trujillo et al 2011;Huang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to have a non-negligible effect on inferred size evolution, and is able to explain part if not all of the observed size evolution (e.g. Saglia et al 2010;Valentinuzzi et al 2010b;Carollo et ρ=−0.26 p=0.14 Figure 13. Dependence of ratio of mass-weighted to light-weighted sizes on different galaxy parameters.…”
Section: Evolution Of the Ratio Of Mass-weighted To Light-weightedmentioning
confidence: 97%